46‐2: Invited Paper: Strip‐Helix‐Fiber Architecture for Stretchable TFTs and Circuits. Issue 1 (28th June 2022) - Nathan, Arokia; Yu, Jun; Jiang, Chen; Ma, Hanbin
Abstract : This paper reviews design considerations for ultralow power thin‐film transistor and amplifier circuits with high stretchability for newly emerging wearable applications. To achieve high stretchability, the device/circuit is layered on an active strip fiber that is coiled in a helical pattern around a core carrier‐fiber. This results in a helical strain of the device/circuit to below 1% despite the core carrier‐fiber being subject to an external strain of 50%. The active helical strip fiber architecture comprises a low‐voltage organic thin‐film transistor and amplifier operating in deep‐subthreshold regime. The thin film transistor and amplifier is layered entirely using inkjet printing technology. The highly stretchable amplifier has a high voltage gain of 214 V/V with subthreshold transconductance efficiency of 0. 6q/kT and ultralow power consumption of 681 pW.